Identification of potassium channel proteins Kv7.2/7.3 as common partners of the dopamine and glutamate transporters DAT and GLT-1 - Bartolomé Martín, David; Ibáñez, Ignacio; Piniella, Dolores; Martínez Blanco, Elena; Pelaz, Sara G.; Zafra, Francisco (My University, 2019)
Dopamine and glutamate transporters (DAT and GLT-1, respectively) share some biophysical characteristics, as both are secondary active carriers coupled to electrochemical ion gradients. In order to identify common or specific components of their respective proteomes, we performed a proximity labelling assay (BioID) in the hippocampal cell line HT22. While most of the identified proteins were specific for each transporter (and will be analyzed elsewhere), we detected two membrane proteins in the shared interactome of GLT-1 and DAT: the transmembrane protein 263 (Tmem263) and the potassium channel protein Kv7.3. However, only Kv7.3 formed immunoprecipitable complexes with GLT-1 and DAT in lysates of transfected HEK293¿cells. Moreover, either DAT or GLT-1 co-clustered with Kv7.2/7.3 along the axonal tracts in co-transfected primary neurons, indicating a close spatial proximity between these proteins. Kv7.3, forming heterotetramers with the closely related subunit Kv7.2, underlies the M-currents that control the resting membrane potential and spiking activity in neurons. To investigate whether the presence of the potassium channel affected DAT or GLT-1 function, we performed uptake determinations using radioactive substrate and electrophysiological measurements. Uptake through both transporters was mildly stimulated by the presence of the channel, an effect that was reversed by the potassium channel blocker XE-991. Electrophysiological recording (in transfected HT22 and differentiated SH-SY5Y cells) indicated that the depolarizing effect induced by the presence of the neurotransmitter was reverted by the activity of the potassium channel. Altogether, these data suggest a tight spatial and functional relationship between the DAT/GLT-1 transporters and the Kv7.2/7.3 potassium channel that immediately readjusts the membrane potential of the neuron, probably to limit the neurotransmitter-mediated neuronal depolarization. This article is part of the issue entitled ¿Special Issue on Neurotransmitter Transporters¿.